AB1111-HPR Validity of Canadian Occupational Performance Measurement in Patients with Upper Limb Disorders in Turkey. (15th July 2016) - Tonga, E.
Abstract : Background: The Canadian Occupational Performance Measure (COPM) 1 was developed to identify and prioritize patient-specific occupational problems and evaluate changes in these problems. In literature on the COPM, consensus exists about the feasibility of the COPM as an instrument to identify a wide range of problems in daily activities. 2, 3 There is only one research that investigate the validity of COPM with Disabilities of Shoulder arm Hand Questionnaire (DASH) in upper limb disorders. 4 This study did not showed the correlations between COPM and DASH, only reported the percentages. Objectives: The aim of our study was to determine the construct validity of COPM by investigating the correlations with two different upper limb functional questionnaires in Turkish patients with upper limb problems. Second aim of our study was to determine the occupational performance problems specific to upper limb in Turkish culture. Methods: Physical therapy outpatients (n=l02, 70% female, age 49.1±16.6) with upper limb disorders were consecutively recruited. All participants completed the the Upper Limb Functional Index Turkish (ULFI-Tk) and the DASH Turkish-version (DASH-Tk) criterion. COPM was conducted by qualified therapist who has 5 year experience of using COPM. Pearson correlation analyses were done between COPM and DASH-Tk, ULFI-Tk. Results: The COPM performance demonstrated statistically significant relationship with DASH-Tk disability scores (r=-0.217;p=0.02) and with ULFI-Tk (r=-0.290; p=0.003). There were also significant relationship between COPM satisfaction scores and DASH-Tk disability (r=-0.220;p=0.02), ULFI-Tk (r=-0.309; p=0.002). Totally 216 activity performance problems (self-care: 80, productivity:71, leisure: 65) determined with COPM. Conclusions: The results of our study demonstrated that COPM is valid assessment in upper limb disorders. Our study was showed performance problems of patients with upper limb disorders that related with Turkish culture. References: Law M et al. Canadian Occupational Performance Measure. Toronto (Canada): Canadian Association of Occupational Therapists; 2005. Kjeken I, Slatkowsky-Christensen B, Kvien TK, Uhlig T. Norwegian version of the Canadian Occupational Performance Measure in patients with hand osteoarthritis: validity, responsiveness, and feasibility. Arthritis Rheum. 2004;51(5): 709–15. Mieke G. Nieuwenhuizen, Canadian Occupational Performance Measure performance scale: Validity and responsiveness in chronic pain. Journal of Rehabilitation of Research and Development 2014, 51(5):727–746. Veehof MM et al. Psychometric qualities of the Dutch language version of the Disabilities of the Arm, Shoulder, and Hand questionnaire (DASH-DLV). J Hand Ther. 2002; 15(4):347–54. Tonga E et al. Cross-Cultural Adaptation, Reliability and Validity of The Turkish version of the Upper LIMB Functional Index (ULFI). Journal of Hand Therapy 2015;28(3):279–85 Disclosure of Interest: None declared